2020
DOI: 10.5005/jp-journals-10006-1779
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome in HELLP Syndrome: An Observational Study

Abstract: Objective: HELLP syndrome (hemolysis, elevated liver enzymes, and low platelets) is a component of hypertensive disorders of pregnancy that is associated with significant maternal and perinatal morbidity and mortality. HELLP syndrome is regarded as a high risk for the mother and neonate compared to preeclampsia. Aims: This study evaluates the maternal and perinatal outcome in HELLP syndrome so that the management is improved resulting in reduced mortality and morbidity. Materials and methods: It is an observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a study by Ni and Cheng on early-and late-onset preeclampsia, concluded that the early-onset preeclampsia is a distinct and more severe clinical entity with earlier gestational age onset and delivery. [4][5][6] In our study, the significant association was found between the decreased SpO 2 level and adverse maternal outcome (p < 0.0001). Srivastava et al, in their study found that SpO 2 successfully predicted adverse maternal outcome.…”
Section: Discussionsupporting
confidence: 54%
“…In a study by Ni and Cheng on early-and late-onset preeclampsia, concluded that the early-onset preeclampsia is a distinct and more severe clinical entity with earlier gestational age onset and delivery. [4][5][6] In our study, the significant association was found between the decreased SpO 2 level and adverse maternal outcome (p < 0.0001). Srivastava et al, in their study found that SpO 2 successfully predicted adverse maternal outcome.…”
Section: Discussionsupporting
confidence: 54%
“…These adverse/poor outcomes have previously been documented and underline the role hypoalbuminemia plays in HELLP syndrome. 3,[5][6][7][8][21][22][23] The current study was limited by its retrospective nature so that it could not determine the causal impact of hypoalbuminemia on maternal and perinatal outcomes among the HELLP cases. Furthermore, since it is a single-institution study, the number of patients included is also rather limited and may result in an inadequately powered study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, some scholarly opinion believe that the syndrome may evolve as a separate entity since it can manifest without preexisting features of severe preeclampsia as a precursor condition. 3,4 The syndrome is one of the dreaded complications with the potential for catastrophic consequences in pregnancy associated with high maternal and perinatal morbidity and mortality. [4][5][6] The cardinal underlying pathophysiology of HELLP syndrome is poorly understood and ill-defined to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation